11 Caring for patients in a faith based setting: demonstrating a model for 'hard to reach' communities and achieving preferred place of death. Issue 3 (1st September 2017) - Craig, Rachel; Tookman, Adrian; Gishen, Faye
Abstract : Introduction: A Marie Curie review 1 highlighted that the Jewish population, alongside Black and Minority Ethnic (BME) groups, are under-represented in utilising palliative care. 2 Explanations may include concerns around gaining trust and being culturally understood. Preferred Place of Death (PPoD) has been used as a key performance indicator (KPI) for measuring effective palliative care. Aim: To establish a palliative care outreach clinic in a faith-based setting and subsequently evaluate patient experience and measure the KPI of PPoD. Methods: In 2011 a cancer charity supporting the Jewish community, in collaboration with Marie Curie and The Royal Free London NHS Foundation Trust, developed a palliative care clinic, serving an area with a large Jewish population. The clinic runs weekly. A palliative care consultant sees and discusses all patients at the Marie Curie multidisciplinary team meeting. Data was collected via anonymous semi-structured patient experience survey in 2013 and 2016 and all patients are offered Advance Care Planning, including PPoD. Actual place of death has been recorded for all deceased patients. Results: 39 patients completed the survey. 100% rated the service 'excellent' or 'good' In 2016, 17 patients in the service died. 13 achieved their PPoD (76%). Conclusion: Achieving a 76% PPoD contrasts with the London average of 38.1% deaths in usual place of residence. 3 This demonstrates the success of a faith based service catering for a traditionally 'hard to reach' population and represents a unique model within the United Kingdom. This model could be extended to other faith based communities to broaden access to palliative care. References: 1. https://www.mariecurie.org.uk/globalassets/media/documents/policy/policy-publications/june-2013/palliative-and-end-of-life-care-for-black-asian-and-minority-ethnic-groups-in-the-uk.pdf 2. Dorff E. End of Life; Jewish Perspectives. The Lancet 2005;366:862–5 3. https://www.endoflifecare.org.uk/data_sources/place_of_death